Prevalence of non-coeliac gluten sensitivity and assessment of the response to gluten-free diet in a cohort of patients with fibromyalgia. (28th July 2022) - Almirall, Miriam; Casellas, Francesc; Dot, Joan; de Torres, Inés; Segurola, Hegoi; Marsal, Sara
Abstract: Objectives: To establish the prevalence of non-coeliac gluten sensitivity (NCGS) in a cohort of fibromyalgia patients and to evaluate their clinical response to a six-week gluten-free diet (GFD), the improvement in their symptoms, the percentage of diet responders who did not fulfil the diagnostic criteria for NCGS and the baseline characteristics that were associated with diet response and diagnostic criteria fulfilment. Methods: Uncontrolled prospective experimental study in a cohort of patients with fibromyalgia from a specialized hospital unit. The percentage of patients that fulfilled the Salerno Experts' Criteria, that responded to GFD, that improved their symptomatology and baseline characteristics associated with GFD response and diagnostic criteria fulfilment was analysed. Results: In total, 142 patients were selected and a NCGS prevalence of 5.6% was observed. A total of 21.8% responded to GFD due to their improvement in intestinal symptoms. In total, 74.2% of the responders did not fulfil the Salerno Experts' Criteria. The presence of diarrhoea and intraepithelial lymphocytosis and lower levels of anxiety were predictive factors of GFD response. No predictive factors of NCGS criteria fulfilment were found due to the low number of discriminators between gluten and placebo. Conclusions: A NCGS prevalence similar to that estimated in the general population was found. A GFD cannot be systematically recommended to all patients with fibromyalgia, although it could be evaluated in those with diarrhoea or intraepithelial lymphocytosis to evaluate if there are improvements in their intestinal symptoms.